Leroy Brown and John Williams operating automatic banding machine at Hercules Hopewell plant - Hercules Incorporated (1951)
General view of Leroy Brown and John Williams operating an automatic banding machine in the Cellulose Department at the Hercules Powder Company plant in Hopewell, Virginia. Per notations accompanying the photograph, the machine applied bands under fixed pressure and then cut and welded the steel strapping. The stacks of banded material visible in the photograph are likely chemical cotton, a form of purified cellulose produced at the Hopewell plant. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Employees; Chemical industry; Cotton; Hercules Incorporated; Corporations; African Americans; Cellulose; African American men; Machinery; Brown, Leroy; Williams, John